Central Venous Disease in Hemodialysis Patients: A Comprehensive Systematic Review of Pathophysiology, Management, and Outcomes - Edelwis Christine; Charles Sanjaya (The International Journal of Medical Science and Health Research, 2025)
INTRODUCTION: Central Venous Disease (CVD), encompassing stenosis and occlusion of major thoracic veins, represents a critical challenge in the management of hemodialysis (HD) patients. It is a leading cause of vascular access dysfunction, contributing to significant morbidity, inadequate dialysis delivery, and compromised quality of life. This review systematically evaluates the evidence base for the pathophysiology, diagnosis, and management of CVD in this vulnerable population. METHODS: A systematic literature search was conducted across PubMed, Google Scholar, Semanthic Scholar, Springer, Wiley Online Library for cohort studies, randomized controlled trials (RCTs), and systematic reviews published between 1995 and 2024. Studies were included if they evaluated risk factors or treatment outcomes for CVD in adult HD patients. Primary outcomes analyzed were technical success, clinical success, primary patency, assisted-primary patency, and secondary patency. Secondary outcomes included complication rates and re-intervention frequency. Study quality was assessed using the Cochrane Risk of Bias tool for RCTs and the Newcastle-Ottawa Scale for observational studies. RESULTS: Seventeen studies met the inclusion criteria for detailed outcome analysis, supplemented by numerous others for epidemiological and pathophysiological context. The evidence overwhelmingly identifies prior central venous catheter (CVC) placement as the principal risk factor for CVD, with risk increasing with catheter duration and number of placements. Endovascular therapy is the first-line treatment for symptomatic lesions. Comparative analysis revealed that while percutaneous transluminal angioplasty (PTA) has high initial success, it suffers from poor long-term primary patency (21-29% at 12 months). Stent grafts (SGs) demonstrate significantly superior primary patency (84-100% at 12 months) compared to both PTA and bare-metal stents (BMS). Drug-coated balloons (DCBs) show promise over PTA but require further validation in central venous anatomy. Surgical bypass remains a viable salvage option for refractory cases. DISCUSSION: The pathogenesis of CVD is a CVC-driven process of endothelial injury and neointimal hyperplasia, exacerbated by high access flow. The management paradigm has shifted from PTA-dominant strategies to a more durable, device-oriented approach, with SGs offering the best primary patency. However, high rates of re-intervention across all modalities underscore the recalcitrant nature of the disease, highlighting a critical need for preventative strategies centered on CVC avoidance. CONCLUSION: CVD is a frequent and serious complication in HD patients, primarily caused by CVCs. While endovascular interventions can effectively manage symptomatic lesions, SGs provide the most durable outcomes. The cornerstone of management should be prevention through timely creation of permanent vascular access.